Offering nicotine patches to all households in a community with high smoking rates: Pilot test of a population-based approach to promote tobacco cessation - Cunningham, John A; Leatherdale, Scott T; Chaiton, Michael; Tyndale, Rachel; Schell, Christina; Godinho, Alexandra (International Journal of Population Data Science, 2021)
Background The objective of this project is to determine the effectiveness of targeting a community with a high smoking rate with the distribution of free-of-charge nicotine patches in order to promote tobacco cessation. Methods/Design One small community with an elevated smoking rate (compared to national and provincial averages) has been identified. All households in the community will be sent a letter offering one smoker (18 years or older; 10 or more cigarettes per day) in the household a free-of-charge mailed five-week supply of nicotine patches (up to a total of 800 five-week kits will be available for distribution). Participants receiving nicotine patches will be asked to complete a six-month follow-up survey assessing tobacco cessation defined as 30-day point prevalence abstinence. In addition, attempts will be made to employ ongoing national population surveys containing cigarette smoking variables to compare changes in smoking prevalence in the target community to other communities with similar characteristics. Discussion We will examine whether the concentrated distribution of mailed nicotine patches will result in a measurable reduction in smoking rates in the target community. If demonstrated, this would provide support for the targeted population-level distribution of an effective individual-level public health intervention. Clinical Trials registration NCT04534231